A new proposed features of Malaysian legal framework for alternative dispute resolution in the tribunal for consumer claims / Su’aida Safei and Nuraisyah Chua Abdullah - Safei, Su’aida; Abdullah, Nuraisyah Chua (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
The Tribunal for Consumer Claims (TCC), is established under section 85, Part XII of the Consumer Protection Act 1999 [Act 599] (CPA). Given the application of ADR under section 107 of the CPA, the vagueness of the provision, as regards the type of ADR to be applied in the TCC, is an issue raised on top of other issues surrounding the decision-making of the President of the TCC and unequal ability of the parties in negotiating their dispute without the supervision of the said President. In the absence of comprehensive discussions on the legal framework of the TCC in the existing literature, the main objective of this paper is to propose a workable ADR for the TCC to adopt in view of the issues faced by the TCC. Using the content analysis, doctrinal legal research, and comparative study with Singapore’s Small Claims Tribunal, this paper provides new suggestions in the management of the TCC, such as case management, flexible numbers of Presidents, given the complexity of cases in the TCC and types of ADR being identified as facilitative mediation and evaluative mediation. These are possible innovations in the legal framework of the TCC, hence providing the practical implication of this paper. The findings of this paper also add to the body of knowledge in the domain of ADR at the TCC and expand the current literature. Most significantly, the findings of this paper answer its main objective by proposing a workable ADR for the TCC to implement, thereby enhancing the TCC's professional practice and satisfying the relevance of this study in terms of professional application.